Istinbath Hukum Imam Syafi’i dalam Pemecahan Kasus Pelecehan Seksual di Indonesia - Muh. Aqsho Che Athoriq. R; Ferdiansa Putra; Rangga Mahesa; Kurniati Kurniati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This study examines the legal istinbath method applied by Imam Syafi'i, especially in the context of solving sexual harassment cases in Indonesia. Legal identity, which etymologically means the excavation of law by deep reasoning, is used to determine the law in matters that are not directly regulated by the Qur'an and Hadith. Imam Shafi'i, through his major works such as "Al-Umm" and "Al-Risalah," explains the basic principles and methodologies used to establish the law by incorporating the main sources of Islamic law, namely the Qur'an, Hadith, Ijma', and Qiyas. This study uses a qualitative method with descriptive analysis of primary and secondary sources, including books and scientific articles that discuss the istinbath method of Imam Shafi'i. The results of the study show that the legal principles generated by this method are very relevant and adaptive in dealing with modern cases such as sexual harassment, which is often triggered by patriarchal culture. Imam Shafi'i's method of legal istinbath, which prioritizes the hierarchy of legal sources and the use of sharp reason, has proven to be able to adapt to the times and continues to be useful in solving modern legal problems. This research also highlights the views of contemporary scholars who provide a new interpretation of this classical method, demonstrating the relevance and effectiveness of the legal istinbath method in dealing with contemporary issues. Thus, this study concludes that the istinbath method of Imam Shafi'i law is a very useful tool to ensure justice and benefits in solving sexual harassment cases in the modern era.